Remote meta C–H bond functionalization of 2-phenethylsulphonic acid and 3-phenylpropanoic acid derivatives. Issue 96 (15th November 2016) - Modak, Atanu; Mondal, Anirban; Watile, Rahul; Mukherjee, Semanti; Maiti, Debabrata
Abstract : This discovery illustrates selective meta C–H bond activation from multiple non-equivalent C–H bonds present in medicinally relevant arylethanesulfonic acid and the 2-arylpropanoic acid moiety using weakly coordinating nitrile as a directing group. Abstract : This discovery illustrates selective meta C–H bond activation from multiple non-equivalent C–H bonds present in medicinally relevant arylethanesulfonic acid and the 2-arylpropanoic acid moiety using weakly coordinating nitrile as a directing group. Transformation of the meta olefinated compounds to important organic molecules has been demonstrated. Efforts were made to obtain mechanistic detail of the meta C–H bond functionalization reaction.